POWTOON FOR THIRD GRADERS: AN IMPLEMENTATION - Putra, Anak Agung Gede Suarjaya (International Journal of Language and Literature, 2019)
In the past, using a conventional media was basic ways to transfer information from the teacher to students. In the era of technology, it is needed to teach using digital media. Therefore, PowToon was implemented as teaching media and it aimed to know the students’ response as well. This research was focused on the implementation and evaluation of the developed PowToon. The data were collected through interview, observation and questionnaire. The result was, developed PowToon could be used to teach English for third-grade students. The media was categorized good based on the result of teacher interview. In relation with the rating of the media combined with the observation checklist, it was found that the implementation could help the teacher in teaching process. From the students’ questionnaire, it was found that the animation video could attract the students’ attention, and it also motivated the student during teaching and learning process.